Determining the Methanol Deuteration in the Disk Around V883 Orionis with Laboratory Measured Spectroscopy - Shaoshan Zeng; Jae-Hong Jeong; Takahiro Oyama; Jeong-Eun Lee; Yao-Lun Yang; Nami Sakai (The Astronomical Journal)
Deuterium fractionation, as studied through mono-deuterated methanol, is frequently used as a diagnostic tool to trace the physical conditions and chemical evolution of interstellar sources. This study investigates methanol deuteration in the disk around V883 Ori, utilising recent laboratory spectroscopic data for CH _2 DOH and CH _3 OD along with Atacama Large Millimeter/submillimeter Array observations. The derived column densities for CH _2 DOH and CH _3 OD are (5.14 ± 0.08) × 10 ^16 cm ^−2 and (4.22 ± 0.06) × 10 ^16 cm ^−2 , respectively. The analysis demonstrates the influence of spectroscopic data on determining molecular column density, excitation temperature, and, most importantly, the inferred D/H ratio. The D/H ratio for CH _2 DOH is calculated to be (7.3 ± 1.5) × 10 ^−3 after applying a statistical correction, while the D/H ratio for CH _3 OD is (1.79 ± 0.36) × 10 ^−2 . The discovery of an unexpectedly low CH _2 DOH/CH _3 OD ratio (1.22 ± 0.02) in V883 Ori, however, raises further questions about the synthesis and chemical processes involved in CH _3 OD formation. Overall, this study underscores the importance of accurate spectroscopic data for studies of isotopic fractionation and provides new insights into methanol deuteration chemistry in star-forming regions. Future research, combining updated spectroscopy and chemical modeling, will help further constrain these processes across different masses and evolutionary stages.